NOVA GENERALIZAÇÃO PARA A CLASSE BETA-G DE DISTRIBUIÇÕES DE PROBABILIDADE - SOUZA, Glaucia Tadu de; OLIVEIRA JUNIOR, Wilson Rosa de; BRITO, Cícero Carlos Ramos de; GOMES-SILVA, Frank Sinatra; SILVA, Ronaldo Venâncio da (Brazilian Journal of Biometrics, 2017)
We propose a new generator of continuous distributions with three extra parameters called the Beta (θ(1 - G); (1 - θ)G + θ), which generalizes the Beta-G class. A special case is presented. The new density function can be expressed as a difference of linear combinations of exponentiated densities based on the same baseline distribution. Various structural properties of the new class, which hold for any baseline model, are derived including explicit expressions for the moments of order n, the moment generating function, the characteristic function, central moments of order n, the general coefficient, the mean deviations, residual life function, reverse residual life function and order statistics. We discuss estimation of the model parameters by maximum likelihood and provide an application to a real data set.